PENERAPAN METODE BERMAIN PERAN MAKRO DALAM MENGEMBANGKAN BAHASA PADA ANAK USIA 4-5 TAHUN DI PAUD KARANGSARI III TELUKJAMBE BARAT - Kurniasih, Kurniasih; Sulaeman, Devi; Riyadi, Ahmad (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
This study aims to improve the language development of children aged 4–5 years through the implementation of the macro role-playing method at PAUD Karangsari III, Telukjambe Barat, Karawang Regency. The background of this research is the low expressive language ability among children, as indicated by limited vocabulary, difficulty in constructing sentences, and challenges in expressing desires and emotions. The study employed a Classroom Action Research (CAR) approach conducted in two cycles, each consisting of planning, action, observation, and reflection stages. The research subjects where 15 children in Group A. Data were collected through observation, documentation, and assessments of language development. The results showed a significant improvement in children’s language abilities in terms of vocabulary, sentence structure, and the use of language in social contexts. These findings indicate that the macro role-playing method is effective in stimulating early childhood language development. Therefore, this method is recommended as a creative and enjoyable learning strategy in early childhood education.